THE POTENTIALS AND CHALLENGES OF INDONESIAN NURSES TO USE ENGLISH IN THE HOSPITAL: A CASE STUDY IN A NEWLY INTERNATIONALLY ACCREDITED HOSPITAL IN INDONESIA - Perti Rosanda; Edwin Zehner; Wipawan Pensuksan (Linguists : Journal Of Linguistics and Language Teaching, 2018)
It not uncommonly known that Indonesia is among countries with English is a foreign language or in other words English is not the language of instruction. As the effect of globalization, the importance of English in Indonesia comes to the growing seen from the increased needs of English such as the language competency is one of core requirements to get certain jobs or academic degrees. The current goal of Indonesia government is to follow the lead of neighbor countries in the 21st century trend in tourism and health which is interchangeably called “medical tourism” or “health tourism”. It proves to pull millions of dollars annually to its destination countries. At some point, English language competency can be assumed to play significant roles in medical tourists’ choices of destinations. This study discusses Indonesia’s potential to become an additional medical tourism destination, as indicated by recent government policy declarations. The author investigated this issue by studying a public hospital in Indonesia that was recently internationally certified approximately two years ago. The study focuses on potentials and challenges of Indonesian hospital nurses in fulfilling the demands of English language competency. Research methods included use of questionnaires, along with semi-structured and informal interviews. In the potential aspect, the nurses reported that they valued English as useful in their jobs even though they admitted that most of them were still less proficient.  The willingness to learn and the attempt to improve English in the workplace had been seen as a potential. Moreover, nurses suggested ways that the institution and government can do to help them with the English improvement. The overall finding is that Indonesia appears to be trying hard to improve its readiness for medical tourism. The findings could also reflect the situations in countries where English is a foreign language in struggling to fulfill the demands of nurses’ competency in the 21st century.